Oral histories and postcolonial memories: towards a multi-vocal narrative of the Algerian war of independence - Brazzoduro, A (Cambridge Scholars Publishing, 2016)
This volume is structured into six chapters, each written by a different author focusing on a single North African, Maghreb and Mashrek country's colonial legacy to investigate borders in a transnational perspective.